Pengaruh Kemampuan Berpikir Kritis Siswa dalam Pembelajaran Matematika - Reskinda Ramadhani; Lintang Kusumawardani; Hazna Dyah Ekaputri; Intan Suryaningrum; Wieline Dewi Azzahra; Nabila Khoirunnisa (Jurnal Lensa Pendas, 2023)
The purpose of this study was to determine students' critical thinking skills and solve math problems in the lower grades of elementary school. This type of research is quantitative descriptive research. Determination of samples and representatives in this study is to use non-probability sampling techniques with saturated sampling techniques because the number of small population is less than 20 people. The sample of this research was class II students at SDN 02 Karangwage, totaling 19 students. In this study using a questionnaire with a total of 6 questions to test students' criticality in thinking and solving math problems in the lower grades of elementary school. The data used in analyzing is the t one sample test with the help of the SPSS application. The results of this study showed that most of the students already had the ability to think critically to solve math problems as evidenced by scores that were higher than KKM (> 75). However, there is still 1 student whose score is not too high from the KKM, which is 75.5 of the total scores obtained by their friends. Based on these data it is concluded that the value of t count = 6.649 and also sig.(2-tailed) obtained is 0.000, which means the value of sig.(2-tailed) < 0.05 then H0 is rejected. So that students' critical thinking skills affect the results of learning mathematics.